The 7th National Gastric Cancer Academic Conference: focus on translational research in gastric cancer - Wu, Aiwen; Ji, Jiafu (Chinese Journal of Cancer Research, 2012)
Gastric cancer is a heterogeneous disease with large variations across geographical regions (1). Although the global incidence of gastric cancer is declining, it remains highly prevalent in Asia as compared to the West (2,3). China is one of the countries with the highest incidence of gastric cancer, and accounts for over 40% of all new gastric cancer cases in the world (4,5). Gastric cancer is the third leading cause of cancer mortality in China (6,7).